2017
DOI: 10.1016/j.jbtep.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Imagery rescripting as a clinical intervention for aversive memories: A meta-analysis

Abstract: Our findings indicate that ImRs is a promising intervention for psychological complaints related to aversive memories, with large effects obtained in a small number of session.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
151
1
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 197 publications
(187 citation statements)
references
References 48 publications
10
151
1
11
Order By: Relevance
“…Instead, the key mechanism of change could be to develop alternative memory representations, through whatever means, that have the retrieval advantage over distressing representations (Brewin, 2006). For example, there are indications that imagery rescripting may be beneficial in PTSD, even though it does not involve fully recontextualising the perceptual memory representation, and instead focuses on encoding a new, less distressing representation (Morina et al, 2017). Interestingly, two recent trials of trauma-focused therapy for PTSD in psychosis found that exposure and EMDR, but not cognitive restructuring, were effective in reducing posttraumatic stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, the key mechanism of change could be to develop alternative memory representations, through whatever means, that have the retrieval advantage over distressing representations (Brewin, 2006). For example, there are indications that imagery rescripting may be beneficial in PTSD, even though it does not involve fully recontextualising the perceptual memory representation, and instead focuses on encoding a new, less distressing representation (Morina et al, 2017). Interestingly, two recent trials of trauma-focused therapy for PTSD in psychosis found that exposure and EMDR, but not cognitive restructuring, were effective in reducing posttraumatic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Following this, it appears imagery modification purely aiming to elaborate contextual representations in Tanya’s episodic memory, as in traditional exposure approaches, may not be helpful because her memory is already contextualized (Foa et al, 2007). Instead, it may be more useful to focus on developing new episodic representations of her intrusive memories, using techniques such as competitive memory training and imagery rescripting (Steel et al, 2015; Morina et al, 2017). …”
Section: Pathways From Victimization To Psychosis: Vignettesmentioning
confidence: 99%
“…IMRS has typically been one component of a broader cognitive-behavioural intervention, with research supporting the effectiveness of the intervention as a whole (Arntz, 2012;McEvoy et al, 2015). However, in a recent metaanalysis by Morina, Lancee, and Arntz (2017), 19 trials of IMRS as a standalone intervention were reviewed. The trials targeted a range of disorders, including post-traumatic stress disorder (n = 8), social anxiety (n = 6), body dysmorphic disorder (n = 2), depression (n = 1), bulimia (n = 1), and obsessive-compulsive disorder (n = 1).…”
Section: Imagery Rescriptingmentioning
confidence: 99%
“…Notwithstanding, the growing evidence suggests ImRs is an efficacious treatment [21, 39]. Recent research has also supported its effectiveness in treating complicated PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…ImRs in the context of adverse childhood memories has been successfully applied to the treatment of disorders such as social anxiety, simple phobias, bulimia nervosa and depression, showing good treatment effects [39]. Taken together, the evidence supports ImRs as an efficacious treatment for PTSD and for addressing aversive childhood memories.…”
Section: Introductionmentioning
confidence: 99%